(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
This paper aims to analyze how the so-called ‘new generation’ European Union trade agreements can impact sustainable development policy of third countries, verifying whether such agreements are endowed with effective instruments that guarantee the implementation of the international commitments assumed with the aim to improve environmental and labour standards. In this sense, the presence of a specific dispute resolution instrument for the chapter on “Trade and Sustainable Development”, distinct from the one provided for the commercial part, on one hand highlights the relevance of the differentiated treatment granted to such issues. On the other hand, it also denotes the fragility of a system based solely on cooperation, which does not provide for the direct imposition of any type of sanction. Given this scenario, the purpose of this study is to reflect on the limitations and potential of ‘new generation’ trade agreements concerning the promotion of sustainable development in third countries and the possible ways to overcome the challenges inherent in building an economical sustainable society.